1998
DOI: 10.1007/bf02708093
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of rules of origin

Abstract: F13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…With the apparent aim of preventing trade deflection, rules of origin can be used to protect a domestic industry from unwanted competition based in the partner, even in conditions where trade deflection is unlikely (Falvey and Reed (1998)). Note that in this situation the EU is unlikely to exert pressure on the trade partner for the general liberalisation of tariffs against other trading partners.…”
Section: The Role Of Rules Of Originmentioning
confidence: 99%
“…With the apparent aim of preventing trade deflection, rules of origin can be used to protect a domestic industry from unwanted competition based in the partner, even in conditions where trade deflection is unlikely (Falvey and Reed (1998)). Note that in this situation the EU is unlikely to exert pressure on the trade partner for the general liberalisation of tariffs against other trading partners.…”
Section: The Role Of Rules Of Originmentioning
confidence: 99%
“…It is rules of origin, such as those discussed above, which underlie the analyses of Krueger (1995) and Krishna and Krueger (1995) who demonstrate how rules of origin can act as 'hidden protectionism' and induce a switch in demand in free trade partners from low-cost external inputs to higher-cost partner inputs to ensure that final products actually receive duty free access. With the apparent © Blackwell Publishing Ltd 2003 aim of preventing trade deflection, rules of origin can be used to protect a domestic industry from unwanted competition based in the partner, even in conditions where trade deflection is unlikely (Falvey and Reed, 1998). Note that in this situation the EU is unlikely to exert pressure on the trade partner for the general liberalisation of tariffs against other trading partners.…”
Section: B the Role Of Rules Of Originmentioning
confidence: 99%
“…Cadot et al (2002) provided evidences that ROOs of NAFTA have restricted the chances for market access to NAFTA markets. Krishna and Krueger (1995) and Falvey and Reed (1998) showed that ROOs have strictly increased production costs since ROOs have induced the use of more expensive local intermediate goods, eventually reducing the demand level of intermediate goods of member countries. On the contrary, Rosellon (2000) has shown that the demand of the intermediate goods of member countries is ultimately increased with the strict ROOs.…”
Section: Roos Protective Measuresmentioning
confidence: 98%